Adrenergic receptors in breast cancer: differential effects of α2A and 2C-adrenergic receptor expression on tamoxifen sensitivity in stably transfected luminal MCF-7 cells - Aparicio, Evangelina (2019)
Breast cancer is the most frequently diagnosed and leading cause of cancer death among women worldwide. Epinephrine and norepinephrine, released during stress, bind to 9 different adrenoceptors. Our group has already described (SAIC 2015, poster 660) by in silico analysis in a great database that patients with high expression of Alpha2A-adrenoceptors (A2A-AR) have better disease-free survival than those with lower expression, mainly in luminal tamoxifen-treated ones. Contrarily, a high expression of Alpha2C-AR was associated with worse outcome in luminal B but not in luminal A patients.